PELATIHAN PENGEMBANGAN MODUL P5 BERBASIS BUDAYA SEKOLAH DENGAN ATM PLATFORM MERDEKA MENGAJAR - Hutagaol, Anita Sri Rejeki; Sopia, Nurapni; Olenggius Jiran Dores, Olenggius Jiran Dores (STKIP Persada Khatulistiwa Sintang, 2023)
ABSTRACTStudent-centered curriculum innovation, namely through the Pancasila Student Profile Project module and school culture to overcome challenges and demands for educational quality. This is in line with the foundation of thinking in the development of education. Based on the results of a survey of the Head of the Education Office and the Chair of the Sintang Regency Mathematics MGMP, which consists of 130 teachers, information was obtained that many teachers do not yet have a system for developing project modules, there has never been training and development of project modules for Pancasila student profiles and school culture, something new for teachers, limited government funding, minimal activities to increase teacher competency, minimal mastery and use of ICT in learning, and technological gaps. Utilization of ICT, especially in internet-based mathematics learning with padlets in the form of platforms. Padlet is able to facilitate collaborative and communicative learning, sharing and communicating ideas through audio-visual features. So teachers can share notes with other teachers in the form of links, images, videos and different documents. The implementation of this service activity was carried out over 4 months with 3 stages, namely the preparation, implementation, and monitoring and evaluation stages. The results of the activities showed that teachers' ICT abilities increased, teachers were able to develop teaching modules and P5 modules and they could be implemented well.Keywords: Development Training, Module P5, School Culture,Â ATM Platform, Independent LearningÂ ABSTRAKÂ Inovasi kurikulum yang bserpusat pada siswa yakni melalui modul Projek Profil Pelajar Pancasila dan budaya sekolah guna mengatasi tantangan dan tuntutan mutu pendidikan. Hal ini sejalan dengan landasan pijakan berpikir dalam pembangunan Pendidikan. Berdasarkan hasil survei terhadap Kepala Dinas Pendidikan dan Ketua MGMP Matematika Kabupaten Sintang yang beranggotakan 130 guru, diperoleh informasi yakni banyak guru belum memiliki sistem dalam mengembangkan modul projek, belum pernah ada pelatihan dan pengembangan modul projek profil pelajar pancasila dan budaya sekolah, sesuatu yang baru bagi guru, pendanaan pemerintah terbatas, minimnya kegiatan peningkatan kompetensi guru, minimnya penguasaan dan pemanfaatan TIK dalam pembelajaran, serta gaptek. Pemanfaatan. Pemanfaatan TIK khususnya dalam pembelajaran matematika berbasis internet dengan Padlet berupa platform. Padlet mampu memfasilitasi pembelajaran kolaboratif dan komunikatif, berbagi dan dapat mengkomunikasikan ide melalui fitur-fitur audio-visual. Sehingga guru dapat berbagi catatan dengan guru lain dalam bentuk link, gambar, video dan dokumen yang berbeda. Pelaksanaan kegiatan pengabdian ini dilaksanakan selama 4 bulan dengan 3 tahapan yakni tahap persiapan, pelaksaan, serta monitoring dan evaluasi. Hasil kegiatan diperoleh kemampuan TIK guru meningkat, guru mampu mengembangkan modul ajar dan modul P5 serta dapat diimplementasikan dengan baik.Kata Kunci: Pelatihan Pengembangan, Modul P5, Budaya Sekolah, ATM Platform, Merdeka Belajar